2017
DOI: 10.3847/1538-4357/aa7ddc
|View full text |Cite
|
Sign up to set email alerts
|

APOGEE Chemical Abundances of the Sagittarius Dwarf Galaxy

Abstract: The Apache Point Observatory Galactic Evolution Experiment (APOGEE) provides the opportunity to measure elemental abundances for C, N, O, Na, Mg, Al, Si, P, K, Ca, V, Cr, Mn, Fe, Co, and Ni in vast numbers of stars. We analyze the chemical abundance patterns of these elements for 158 red giant stars belonging to the Sagittarius dwarf galaxy (Sgr). This is the largest sample of Sgr stars with detailed chemical abundances and the first time C, N, P, K, V, Cr, Co, and Ni have been studied at high-resolution in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
129
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(144 citation statements)
references
References 76 publications
12
129
3
Order By: Relevance
“…Abundance measurements were carried out using MOOG (Sneden 1973;v. 2017) with MARCS model atmospheres (Gustafsson et al 2008).…”
Section: Abundance Measurement Methodologymentioning
confidence: 99%
“…Abundance measurements were carried out using MOOG (Sneden 1973;v. 2017) with MARCS model atmospheres (Gustafsson et al 2008).…”
Section: Abundance Measurement Methodologymentioning
confidence: 99%
“…The one possible Figure 3. Overplotted are abundances of (top) Fornax dSph stars reported by (Letarte et al 2010, yellow downward triangles) and (Lemasle et al 2014, yellow upward triangles), (middle) LMC disk (green squares) and bar (green wide diamonds) stars from Van der Swaelmen et al (2013), and (bottom) Sgr dSph and M54 stars (cyan narrow diamonds) reported by Mucciarelli et al (2017). exception is the Sgr dSph, for which the dominant population looks like a possible metal-rich extension of the LMg population (Sbordone et al 2007;Carretta et al 2010;Hasselquist et al 2017).…”
Section: Potential Originsmentioning
confidence: 99%
“…This may suggest that the metal-poor stars in our LMg population and the LMC have had analogous star formation histories, and ones that differ from both lower mass dSph satellites, and some of the more massive dSphs, such as Unfortunately, one of the most massive dSphs and therefore interesting satellites to compare with our Mg populations, the Sgr dSph, has been observed by APOGEE, but has been mostly excluded from our own sample by the stellar surface temperature restriction > T 4000 eff K. So that we maintain as self-consistent a sample as possible, the latter requirement removes the coolest and brightest red giants from our sample, which have been analyzed by ASPCAP using a different grid of model atmospheres. These infrared-bright stars, however, are the only types of red giants that APOGEE has accessed and have data available to analyze in Sgr (e.g., Majewski et al 2013;Hasselquist et al 2017) because of the large distances to this dSph. For the same reason, but also because these younger stars are the dominant red giant population in the system, most other chemical abundance studies of the Sgr dSph also typically observe Sgr's more metal-rich stars (e.g., Sbordone et al 2007;Hasselquist et al 2017).…”
Section: Comparison To Mw Satellitesmentioning
confidence: 99%
See 1 more Smart Citation
“…For a comparison, we use Sgr dSph because this dwarf galaxy is sufficiently enriched to have a considerable M giant population, like TriAnd. To do so, we use a set of 69 Sgr dSph members confirmed by Hasselquist et al (2017) and satisfy our quality criteria.…”
Section: Datamentioning
confidence: 99%